Prevalence and determinants of ideal cardiovascular health by sex and region—a population-based study in Peru - Víctor Juan Vera-Ponce; Víctor Juan Vera-Ponce; Fiorella E. Zuzunaga-Montoya; Fiorella E. Zuzunaga-Montoya; Luisa Erika Milagros Vásquez-Romero; Joan A. Loayza-Castro; Eder Jesús Orihuela Manrique; Mario J. Valladares-Garrido; Mario J. Valladares-Garrido; Mario J. Valladares-Garrido; Carmen Inés Gutierrez De Carrillo; Carmen Inés Gutierrez De Carrillo (Frontiers in Cardiovascular Medicine)
IntroductionAttaining what the American Heart Association terms Ideal Cardiovascular Health (ICVH) is viewed as an essential objective for preventing cardiovascular diseases (CVD).ObjectiveTo determine the prevalence of ICVH, stratified by sex and region and its associated factors in the adult population of Peru.Materials and methodsAnalytical cross-sectional study. Data were obtained from the Life Stage Food and Nutrition Surveillance Survey (VIANEV). ICVH can be depicted vis-a-vis the seven metrics of the AHA: blood pressure levels, total cholesterol and glucose levels, smoking status, body mass index, physical activity levels, and dietary intake through the consumption of fruits and vegetables. The variable was categorized as deficient/moderate vs. ideal for regression analysis.ResultsOf the 863 participants examined, findings demonstrated that 38.01% had ICVH. The prevalence is trending lower in correlation with rising age and educational attainment levels and for those inhabitants residing at higher elevations. Likewise, statistically significant variations were observable concerning the prevalence of ICVH contingent on the region of residence and marital status, in particular amongst the feminine inhabitants.ConclusionsThese results demonstrate that the frequency of ICVH in the grown-up inhabitants of Peru is comparatively tiny. Things linked to a lesser frequency of ICVH involve increased age, a higher level of education, living at higher altitudes, and staying married to a woman. These discoveries underscore the need to implement prevention and treatment strategies for CVD distinct for each inhabitant team.